Case Report: Take a Second Look: Covid-19 Vaccination-Related Cerebral Venous Thrombosis and Thrombotic Thrombocytopenia Syndrome - Braun, Tobias; Viard, Maxime; Juenemann, Martin; Struffert, Tobias; Schwarm, Frank; Huttner, Hagen B.; Roessler, Florian C. (Frontiers in Neurology, 2021)
We present two cases of ChAdOx1 nCov-19 (AstraZeneca)-associated thrombotic thrombocytopenia syndrome (TTS) and cerebral venous sinus thrombosis (CVST). At the time of emergency room presentation due to persistent headache, blood serum levels revealed reduced platelet counts. Yet, 1 or 4 days after the onset of the symptom, the first MR-angiography provided no evidence of CVST. Follow-up imaging, performed upon headache refractory to nonsteroidal pain medication verified CVST 2–10 days after initial negative MRI. Both the patients received combined treatment with intravenous immunoglobulins and parenteral anticoagulation leading to an increase of platelet concentration in both the individuals and resolution of the occluded cerebral sinus in one patient.